Effect of pre-eclampsia on glomerular filtration rate in Sudanese women - Beheiry, Hind Mamoun; Ali, Ibrahim Abdelrhim; Rayis, Duria A. M.; Saeed, Amal M (International Journal of Research in Medical Sciences, 2017)
Background: Creatinine clearance is safest method to measure glomerular filtration rate (GFR) in pregnancy. The objectives was to study a case-control study conducted in Omdurman Maternity Hospital aimed to assess GFR, using creatinine clearance and magnitude of changes of serum creatinine in pre-eclampsia. Methods: Pre-eclamptic were 70, normal pregnant 96 and non-pregnant 63. Investigations were done at St Hellier’s hospital London. Serum and urine creatinine were measured using Jaffé reaction and spectrophotometer. 24-hour urine output was measured and creatinine clearance calculated to find GFR. GFR was calculated in ml/min/mm2 using John Hopkins’ method. Results: The mean serum creatinine in pre-eclamptic (68.6µmol/L) was less than non-pregnant (75.5µmol/L) (P=0.001) but was higher than normal pregnant (62.4µmol/L) (P=0.003). Mean GFR pre-eclamptic (68.6ml/min.1.73m2) was less than non-pregnant (87.0ml/min/1.73m2) (P=0.0001) and normal pregnant (89.0ml/min/1.73ml/min/1.73m2) (P =0.0001). Conclusions: GFR decreased at term in normal pregnancy and even more in pre-eclampsia. Serum creatinine levels increased and did not correlate with GFR changes in pre-eclampsia.